2001
DOI: 10.3109/10611860108997922
|View full text |Cite
|
Sign up to set email alerts
|

Novel Drug Delivery System to Bone Using Acidic Oligopeptide: Pharmacokinetic Characteristics and Pharmacological Potential

Abstract: We synthesized fifteen oligopeptides consisting of Asp or Glu conjugated with a fluorescent probe, 9- fluorenylmethylchloroformate (Fmoc). In the in vitro binding assay to putative hydroxyapatite (HA), the affinities of these conjugates depended only on the number of amino acid residues, not on their optical characters (L or D) or their species (Asp or Glu). In an in vivo experiment involving a single i.v. injection of Fmoc-D-Asp oligopeptides into mice, peptides consisting of over six Asp residues were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 15 publications
0
70
0
Order By: Relevance
“…The uptake level in soft tissues was less than in estradiol. Thus, estradiol with at least six residues of L-Asp was observed to prevent bone loss in ovariectomized (osteoporosis) mice without causing liver damage or increasing uterine weight [61]. Bone density improved with fewer adverse effects, suggesting that estradiol tagged with the acidic oligopeptide is a potential drug to treat a postmenopausal osteoporosis [43].…”
Section: Discussionmentioning
confidence: 96%
“…The uptake level in soft tissues was less than in estradiol. Thus, estradiol with at least six residues of L-Asp was observed to prevent bone loss in ovariectomized (osteoporosis) mice without causing liver damage or increasing uterine weight [61]. Bone density improved with fewer adverse effects, suggesting that estradiol tagged with the acidic oligopeptide is a potential drug to treat a postmenopausal osteoporosis [43].…”
Section: Discussionmentioning
confidence: 96%
“…A drug attached to HA is released during bone resorption processes and targeting a drug to HA is a potential strategy for a selective drug delivery to bone [73,74]. Kasugai et al, 2000 showed that they could enhance estradiol uptake by bone and prevent osteoporosis by tagging the hormone to Glu 6 (E6) [75,76]. We and others have recently applied this new bone-targeting system to a large molecule, an enzyme (tissue nonspecific alkaline phosphatase), showing that the tagged enzymes are delivered more efficiently to bone [77][78][79] and that the tagged enzyme improves clinical and pathological effects of a mouse model of a systemic bone disease, hypophosphatasia, better than untagged native enzyme [80].…”
Section: Long Circulating Ert-a Chemically Modified β-Glucuronidase (mentioning
confidence: 99%
“…The 3-carboxylate and 4-carbonyl groups in quinolone are known to be responsible for potential chelating property with divalent metals such as calcium existing in bone, and these groups remain intact in NFLX-D 6 , but not in LVFX-D 6 (32). It is also known that the extension of the number of acidic amino acid increases the bone accumulating property of acidic oligopeptide in vivo (21). Thus, it was hypothesized that the intact 3-carboxylate and 4-carbonyl groups in NFLX-D 6 further augmented the affinity of L-Asp hexapeptide to bone.…”
Section: Discussionmentioning
confidence: 97%
“…To determine the binding affinity of acidic oligopeptides to hydroxyapatite, homopeptides consisting of two to ten residues of acidic amino acids were conjugated with 9-fluorenylmethylchloroformate and the binding affinities were investigated in vitro. The results indicated that the dissociation constants of the acidic oligopeptides decreased with increasing numbers of acidic amino acid residues, and the maximal binding rates reached a plateau at six residues, which were independent of acidic amino acid specie (Asp or Glu) and optical isomeric form (L or D) (21). In vivo, fluorescein-labeled L-Asp hexapeptide accumulated specifically in bone at 24 h after systemic administration in mice and was not detected in other tissues.…”
Section: Introductionmentioning
confidence: 89%